Analysis of host determining factors in susceptibility to tuberculosis in the South African coloured population - De Wit, Erika (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Biomedical Sciences. Molecular Biology and Human Genetics))--University of Stellenbosch, 2009.